A broadband dual‐polarized magnetoelectric dipole filtering antenna. Issue 12 (14th October 2022) - Lu, Jiaguo; Cao, Yong; Ren, Jian; Hou, RongXu; Zuo, Miaomiao; Zhang, Hongtao; Yin, Yingzeng
Abstract: A broadband dual‐polarized magnetoelectric (ME) dipole filtering antenna is investigated in this letter. The antenna is composed of radiation patches, vertical shorting patches, feed microstrip lines and a ground plane. By properly changing the length of the feeding microstrip line, a radiation null is generated at upper passband edge. On the other hand, by nesting a parasitic patch inside the radiation patch, another radiation null is introduced into the upper passband edge successfully. The utilization of the inherent lower passband edge radiation null of ME‐dipole and the introduction of the aforementioned two radiation nulls make the antenna obtain a good filtering response. For verification, a prototype is designed, fabricated, and relevant measurements are obtained, which agree well with the simulated ones. The measured results show that the antenna achieves a relative bandwidth of 71.4% (2.7–5.7 GHz) and the out of band rejection level is higher than 13.36 dB. Moreover, the antenna has a peak‐realized gain of 8.43 dBi and stable radiation patterns are obtained in the whole passband.